Scratch damage on guiding surfaces of high-speed bearings under oil cut-off condition. (October 2022) - Wang, Che; Zhang, Chuanwei; Bao, Maokuan; Gu, Le; Wang, Liqin; Wei, Xunkai; Li, Wanrong
Highlights: The severe scratch damage on guiding surfaces of high-speed bearing is generated due to the coupling effect of impact and sliding under oil cut-off conditions. Obvious oxidation occurs on the guiding surface of the outer ring due to the tribochemical reactions triggered by the high frictional heat at high-speed sliding contact. Adhesion occurs on the guiding surface of the bearing due to the shear instability of near-surface material with a plastic deformation depth of 15 μm. Abstract: The scratch damage mechanism on guiding surfaces of high-speed bearings due to impact-sliding coupling action under the oil cut-off condition was investigated. The surface topography and element composition on the scratch surfaces were tested. The impact-sliding contact behavior between the cage and outer ring was analyzed by using the finite element method. The results showed that scratch wear with obvious adhesion and oxidation occurred on the guiding surface of the outer ring. Plastic deformation was generated in near-surface layers with a depth of about 15 µm. The thermal shear instability and tribochemical reaction were the root causes of the scratch damage on guiding surfaces. Under the oil cut-off condition, the impact-sliding contact between the cage and ring generated high temperature rise, leading to material softening and surface oxidation. Consequently, adhesion occurred with obvious plastic deformation due to the shear instability of near-surface material at impact-sliding contact.